(untitled) (ENTHYMEMA, 2019)
The essay aims to investigate the connection between phenomenological psychiatry and poetry in the books on “fragile passions” and “nostalgia” of Eugenio Borgna. For him the aesthetic-artistic world has a cognitive value: the literature is not matter of literary criticism or philological attention; literature is rather source, testimony and corroboration of psychiatric knowledge.